STRUKTUR DAN KOMPOSISI VEGETASI RIPARIAN SUNGAI PAGER KECAMATAN RAKUMPIT KOTA PALANGKA RAYA Structure and Composition of Pager River Riparian Vegetation In Rakumpit District, Palangka Raya City: Setiarno*, Santosa Yulianto dan Sandri Wittu - Administrator Journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTRiparian vegetation is easily distracted natural resource due to mankind activities. This study attempts toexamine the species composition, the stand structure, and the species diversity of riparian vegetation on PagerRiver, Rakumpit district, Palangka Raya. The vegetation data were collected through path combination method withgridline. We find out that the plant diversity of all types of growth is 28 species with 16 families. The number ofspecies on station I (upstream) are 13 species with 7 families, while the species having the highest INP is GalamTikus (Syzygium zeylanicum (L) DC). There are 19 species with 11 families on station II (middle) in which Resak(Vatica rassak) has the highest INP. Meanwhile on station III, there are recorded 16 species with 11 families wherethe most dominating species is Balawan (Tristaniopsis stellata Ridl.). The spread of tree diameter of riparianvegetation on Pager river (upstream, middle, downstream) suggests the pattern of reversed "J". Of the upstreamriparian, the species diversity values of all types of growth sit on the low category. Of the middle and downstreamriparian, the diversity values are both low at the seedling and sapling level.Meanwhile, those values are in mediumcategories at the pole and tree level. The species richness generally corresponds to the low category whereas thespecies evenness corresponds to the high category.Keywords: Diversity index, species composition, structure, riparian vegetation